A Decade of Blockchain in Finance: Bibliometric Analysis and Research Directions - M., Satyavathi; Harish Kumar, Kuppili (INTI International University, 2025)
Blockchain technology has rapidly emerged as a transformative force across sectors such as healthcare, supply chains, energy, and voting systems. Its decentralized, transparent, and secure architecture improves efficiency, enhances trust, and reduces costs. Among these domains, finance has experienced the greatest disruption, with blockchain reshaping banking by fostering transparency, security, and efficiency. This study presents a bibliometric analysis of blockchain in finance, mapping trends, patterns, and intellectual trajectories. The analysis explores publication growth, document types, and leading contributors, while identifying the most cited works shaping the field. Using VOSviewer, keyword co-occurrence and bibliographic coupling visualize thematic clusters and intellectual linkages. By synthesizing these findings, the study highlights blockchain’s current research landscape, identifies gaps, and proposes future directions